2011
DOI: 10.1038/ijo.2011.194
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and mortality rate among Hispanic adults: a pooled analysis of multiple epidemiologic data sets

Abstract: OBJECTIVE To evaluate the association between body mass index (BMI, kg m−2) and mortality rate among Hispanic adults. METHODS AND PROCEDURES Analysis of five data sets (total N = 16 798) identified after searching for publicly available, prospective cohort data sets containing relevant information for at least 500 Hispanic respondents (≥18 years at baseline), at least 5 years of mortality follow-up, and measured height and weight. Data sets included the third National Health and Nutrition Examination Survey,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 42 publications
(43 reference statements)
7
31
2
1
Order By: Relevance
“…Our results further confirm addressing food choice as an important primary target for social ecological interventions to address diabetes [21,22]. Future studies may also consider an environmental scan in underserved border communities to examine the availability and affordability of fresh produce and more in-depth qualitative investigations about other contexts [7]. Health promotion efforts addressing community food environments may further contribute to improved dietary outcomes [20].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our results further confirm addressing food choice as an important primary target for social ecological interventions to address diabetes [21,22]. Future studies may also consider an environmental scan in underserved border communities to examine the availability and affordability of fresh produce and more in-depth qualitative investigations about other contexts [7]. Health promotion efforts addressing community food environments may further contribute to improved dietary outcomes [20].…”
Section: Discussionsupporting
confidence: 70%
“…The prevalence of age-adjusted diagnosed diabetes in Mexican American adults in the U.S. is 13.3%, nearly double that of Non-Hispanic Whites (7.1%) [7]. Compared to a national age-adjusted average of 8.2 per 1,000 persons, rates of incident diabetes nationwide are highest among Hispanic men (13.2), Hispanic women (13.1), persons with less than high school education (15.1), those in poverty (11.2), and those who are disabled (14.9) [8].…”
Section: Introductionmentioning
confidence: 99%
“…In one longitudinal study, 983 underweight individuals (BMI < 18.5) with an average age of 75.3 years had higher three-year mortality rates compared with those having higher BMI 16. The association between underweight BMI and mortality has been observed in different ethnic populations, including Hispanics 17. Additionally, underweight patients with congestive heart failure have higher mortality rates compared with individuals having higher BMI 18.…”
Section: Discussionmentioning
confidence: 99%
“…Reference cutoff values for each anthropometric measure were computed by following the prevalence‐matched approach, similar to methods used by Flegal et al . First, we calculated the proportion of adults in our sample that had a BMI ≤ 25 kg/m and a BMI > 25 kg/m. Next, we looked at the distributions of each of the body composition measures and selected a cutoff that would yield the same proportion in our sample to match the distribution based on BMI.…”
Section: Methodsmentioning
confidence: 99%
“…Although studies have shown that elevated BMI consistently associates with mortality in white and black populations , it does not do so among Hispanic adults . Studies have indicated that more precise measures of adiposity, such as ratio measures (e.g., waist‐to‐hip, waist‐to‐thigh, waist‐to‐height), may be stronger predictors of mortality , diabetes , and cardiovascular disease (CVD) than BMI in whites and blacks, while lean mass has been shown to play a protective role in mortality risk .…”
Section: Introductionmentioning
confidence: 99%